Baseband receiver design for wireless MIMO-OFDM communications - Chiueh, Tzi-Dar, 1960-; Tsai, Pei-Yun.; Lai. I-Wei.; Chiueh, Tzi-Dar, 1960-; IEEE Xplore (Online Service); John Wiley & Sons (Hoboken, New Jersey : Wiley, 2012)
The second edition to OFDM Baseband Receiver Design for Wireless Communications , this book expands on the earlier edition with enhanced coverage of MIMO techniques, additional baseband algorithms, and more IC design examples. The authors cover the full range of OFDM technology, from theories and algorithms to architectures and circuits. The book gives a concise yet comprehensive look at digital communication fundamentals before explaining signal processing algorithms in receivers. The authors give detailed treatment of hardware issues - from architecture to IC implementation.. Links OFDM and MIMO theory with hardware implementation. Enables the reader to . transfer communication receiver concepts into hardware. design wireless receivers with acceptable implementation loss. achieve low-power designs. Covers the latest standards, such as DVB-T2, WiMAX, LTE, and LTE-A. Includes more baseband algorithms, such as iterative receiver and mobile OFDM equalization. Contains expanded treatment of channel models and MIMO techniques. Demonstrates concrete design examples of the WiMAX system. Features companion website with lecture slides for instructorsBased on materials developed for a course in digital communication IC design, this book is ideal for graduate students and researchers in VLSI design, wireless communications, and communications signal processing. Practicing engineers in industry working on algorithms or hardware for wireless communications devices will also find this book to be a key reference.Companion website for the book:www.wiley.com/go/chiueh/ofdm2e.
11.5.2 Taiwan High Speed Rail Field Trial 340 -- Summary 341 -- References 341 -- Index 343.
Rev. ed. of: OFDM baseband receiver design for wireless communications / Tzi-Dar Chiueh, Pei-Yun Tsai. c2007.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/22/2015.
Keywords: Radio -- Transmitter-receivers.; Wireless communication systems -- Equipment and supplies; Orthogonal frequency division multiplexing; MIMO systems; Electronic books